Readability in reading materials selection and coursebook design for college English in China - Lu, Zhongshe (2002)
This thesis studies the application of readability in reading materials selection and coursebook design for college English in an EFL context in China. Its aim is to develop rationales which coursebook writers can utilise in selecting materials as texts and as a basis for designing tasks.